2022
DOI: 10.1002/pc.27174
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pore size and layout on mechanical and biological properties of 3D‐printed bone scaffolds with gradient porosity

Abstract: The design of porous gradient scaffolds for bone tissue engineering scaffolds is a relatively new approach. This strategy is based on imitating bone tissue in order to stimulate enhanced cellular responses. An additive manufacturing (AM) method, such as the fused filament fabrication (FFF) system, provides precise and repeatable pore size control. FFF is a well-known AM manufacturing process for producing high-quality parts at a low cost. In this study, polycaprolactone (PCL) and variable hydroxyapatite (HA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Lastly, the sintering temperature effect on the mechanical properties and porosity of scaffolds was measured, and it was shown that when the sintering temperature was raised, the mechanical qualities improved while the porosity decreased. Scaffolds with less porosity are less effective biologically, according to the researchers 51 . When it comes to fixing cracks in skulls, biological activity is more crucial than mechanical qualities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the sintering temperature effect on the mechanical properties and porosity of scaffolds was measured, and it was shown that when the sintering temperature was raised, the mechanical qualities improved while the porosity decreased. Scaffolds with less porosity are less effective biologically, according to the researchers 51 . When it comes to fixing cracks in skulls, biological activity is more crucial than mechanical qualities.…”
Section: Discussionmentioning
confidence: 99%
“…Scaffolds with less porosity are less effective biologically, according to the researchers. 51 When it comes to fixing cracks in skulls, biological activity is more crucial than mechanical qualities. For this reason, the scaffolds sintered at 1150°C were selected for further cell and animal tests due to their optimal combination of biological activity and mechanical qualities.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is highlighted by several review articles detailing recent advances in the additive manufacturing technology space including advances in the area of smart materials, 1 coatings of bio-polymer systems, 2 applications with natural materials for the matrix and the fiber, 3 recent advances in the performance of fiber filled polymer systems for the FFF process. 4 Papers in this special issue range from the use of bio and bio-inspired materials, 2,3,5-12 materials and material systems that benefit from nanoscale enhancements, [13][14][15][16][17][18][19][20][21][22][23] advances in the medical field, [24][25][26] additive material systems utilizing thermosets, [27][28][29] large scale additive manufacturing, [30][31][32] and some rather novel applications in AM. 1,[33][34][35] Several articles focus on improvements for characterization, [36][37][38][39] and quite a few seek to identify parameters to enhance the final part performance through processing improvements.…”
Section: D Printing Additive Manufacturing Polymer Compositesmentioning
confidence: 99%
“…directly affect the efficiency of tissue reconstruction in such a way that all the scaffold traits should be similar to the host tissue. [6] In the case of hard tissue, focusing on bone tissue, the mechanical properties of the scaffolds play an important role in the success of tissue reconstruction. [7] The hydrogels usually have poor mechanical properties due to their porosity and noncompact structures, which cause a preposterous mismatch between natural bone tissue and the scaffolds.…”
mentioning
confidence: 99%
“…with 400 μm strands diameter and an infill of 40%. The linear equation of the model to predict the degradation of the scaffolds for infill and strand diameter is presented in Equations(6)…”
mentioning
confidence: 99%